The Concept of Milieu as the Possibility of Overloading Education as the Territorialization of Anthropocentric Life - Kairė, Sandra (Acta Paedagogica Vilnensia, 2025)
The paper raises the problem of education at a theoretical level as an anthropocentric territorialization of life and seeks to consider the possibility of introducing a philosophical concept of the milieu in education as a possible solution to this problem. The paper examines the interpretation of the milieu concept from a philosophical point of view and discusses the manifestations of the concept of milieu in the field of educational science. It then draws on Linda Knight’s (2016) analysis of the playground as a medium, as well as on other empirical studies actualizing the changes in the child’s relationship to the environment and to non-humans in the context of the Anthropocene epoch with the objective to show how the concept of the milieu complements and highlights the fact that, in the process of education, radical encounters between the different actors can appear, in which the dualities of educator/pupil, teaching/learning, and human/non-human can be dissolved. The paper also argues that the concept of the milieu can help to rethink the fact that learning in specific places (both inside and outside of educational institutions) creates an awareness of the interconnectedness of all organisms and the possibility of experiencing it, which is relevant for the construction of a relationship between human beings and other species, and thus for the reduction of the territorialization of anthropocentric life in education.